2019
DOI: 10.1002/cplu.201900277
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Sensing Performance and Operation Mechanism of Organic π‐Conjugated Materials

Abstract: Organic π‐conjugated materials, which have advantages of tailorable chemical structures, solution processability, and mechanical flexibility, are promising candidates for applications in low‐cost, portable gas sensors that operate at room temperature. Nevertheless, there are still challenging issues in the development of organic semiconductor gas sensors because of issues such as relatively poor sensitivity, slow response, and low recovery. Herein, we summarize the recent progress of gas sensors based on organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 90 publications
(180 reference statements)
0
48
0
Order By: Relevance
“…The observed decrease in I SD is likely due to NH 3 molecules diffusing into the conductive channel at the OSC/dielectric interface and donating electrons via a charge transfer reaction, which decreases the number of charge carriers (holes) . 44 Furthermore, the I SD responses remained stable after five continuous cycles of dynamic ammonia exposure over a period of more than 10 h at various levels of %RH as shown in Figure 3b (Figure S11, Supporting Information, for change in current response vs time). The improved sensitivity at higher RH has been previously assigned to the mixture of ammonia and water forming ammonium hydroxide, which enhances the magnitude of Δ I res / I 0 (%) response of the device 45…”
mentioning
confidence: 99%
“…The observed decrease in I SD is likely due to NH 3 molecules diffusing into the conductive channel at the OSC/dielectric interface and donating electrons via a charge transfer reaction, which decreases the number of charge carriers (holes) . 44 Furthermore, the I SD responses remained stable after five continuous cycles of dynamic ammonia exposure over a period of more than 10 h at various levels of %RH as shown in Figure 3b (Figure S11, Supporting Information, for change in current response vs time). The improved sensitivity at higher RH has been previously assigned to the mixture of ammonia and water forming ammonium hydroxide, which enhances the magnitude of Δ I res / I 0 (%) response of the device 45…”
mentioning
confidence: 99%
“…The application of MPc in gas sensors can be traced back to late 1980s in the pioneering work of Jones et al, reporting the very high responses and ultrafast kinetics (a few s) of PbPc-based chemiresistors towards NO 2 obtained by thermal cycling at 300 °C [ 37 ]. In the subsequent years, extensive reviews on OFET devices utilizing MPc materials were reported [ 8 , 38 ] including one by us which focused in particular on gas sensor applications [ 39 ]. MPc-based chemiresistors were extensively studied by Kummel and coworkers to detect a large group of electron-donating gas analytes [ 40 ].…”
Section: Suitability Of Phthalocyanines In Heterostructure Based Gmentioning
confidence: 99%
“…A common example is OLEDs, which is widely used in new generations of flat panel color displays in products like televisions, monitors, smartphones, tablets and hosts of wearable electronics while OPVs are increasingly being recognized as a potential alternative to conventional expensive silicon-based photovoltaics [ 7 ]. Chemical sensors are another widely researched area inviting numerous studies on organic semiconductors owing to their advantages of low cost and flexibilities of chemical design, synthesis and processing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility makes organic film based electronic devices superior over its inorganic counter parts. For flexible device applications such as power sources [74,75], displays [76], electronics [77], super capacitors [78], gas sensors [79][80][81], thermoelectric power generators [82,83], organic light emitting diodes [84,85], radiation dosimeters [86][87][88] etc., organic semiconductors are promptly used. The nature of interaction between high energy EB and organic materials depends on the energy as well as dose of the incident EB [7].…”
Section: Organic Semiconductors and Its Interaction With Electron Beammentioning
confidence: 99%